Reprogramming tumor-associated macrophages and blocking PD-L1 via engineered outer membrane vesicles to enhance T cell infiltration and cytotoxic functions - Zhiqiang Chen; Bo Wang; Jianwei Zheng; Chao Liu; Peijun Xu; Qianqian Zhou; Jiayong Li; Zijian Shi; Zhenduo Wang; Xuyan Wang; Shunjin Xia; Fangquan Xu; et al. (Journal of Nanobiotechnology)
Abstract The immunosuppressive tumor microenvironment (TME) critically undermines the efficacy of T cell-based tumor immunotherapy by impeding CD8+ T cell infiltration and cytotoxic function, primarily through tumor-associated macrophages (TAMs) and immune checkpoint molecules such as programmed death ligand 1 (PD-L1). Here, we present a multifunctional nanoplatform, IN@OMV-PDL1nb, designed to simultaneously inhibit TAM-derived immunosuppressive metabolite itaconic acid (ITA) by targeting immune-responsive gene 1 (IRG1) and block PD-L1 within the TME. Engineered outer membrane vesicles (OMVs) serve as precision delivery vehicles for the IRG1 inhibitor IRG1-IN-1 (IN) and as carriers for PD-L1 nanobody release, activated by matrix metalloproteinase-2 (MMP-2). IN@OMV-PDL1nb effectively inhibits IRG1 expression in TAMs, thus reducing the accumulation of ITA, restoring chemokines (CXCL9 and CXCL10) secretion, and enhancing CD8+ T cells infiltration within tumors. The released PD-L1 nanobody protects CD8+ T cells, preserving their tumoricidal activity. In murine tumor models, IN@OMV-PDL1nb significantly inhibited tumor growth, increased survival, and enhanced antigen presentation and T cell recruitment. Additionally, IN@OMV-PDL1nb induced robust adaptive immunity, facilitating antigen-specific immune memory that prevented tumor recurrence and metastasis. This dual-targeting approach offers a promising strategy to overcome TME-driven immunosuppression in tumor immunotherapy.